2015
DOI: 10.1002/prep.201400215
|View full text |Cite
|
Sign up to set email alerts
|

Response of TEGDN Propellants to Plasma Ignition with the Same Magnitude of Ignition Energy as Conventional Igniters in an Interrupted Burning Simulator

Abstract: [a] 1Introduction Plasma-propellant interaction had been widely studied to understand the plasma ignition mechanismo fp ropellants [1][2][3][4][5][6][7],a ugmentation burning rate phenomena [8],a nd physical processes [ 9],a nd to benefit the design of the plasma generator to ignite the charge system during the gun or combustion simulator [10].A lso, there are many demonstration tests [11,12] in the electrothermalc hemical gun (ETC) and achieved valuable results to proof the advantage of plasma ignition, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Kappen et al [25] investigated the plasma radiation to the propellant and proposed that the observed structural damage of translucent JA2 (triple-base gun propellant) samples is due to radiation only. Xiao et al [26] proposed that plasma ignition presents a significantly shorter ignition delay and lower ignition energy. There is a stronger ablation and impact interaction of plasma flow with the surface of the propellant.…”
Section: Introductionmentioning
confidence: 99%
“…Kappen et al [25] investigated the plasma radiation to the propellant and proposed that the observed structural damage of translucent JA2 (triple-base gun propellant) samples is due to radiation only. Xiao et al [26] proposed that plasma ignition presents a significantly shorter ignition delay and lower ignition energy. There is a stronger ablation and impact interaction of plasma flow with the surface of the propellant.…”
Section: Introductionmentioning
confidence: 99%
“…With the increase in the TEGDN content ratio, the decomposition heat of NEPE propellants shows obvious decrease and rise under different pressure conditions. [7][8][9] Due to hydrolysis between the nitrate ester and H 2 O, the trace moisture content of TEGDN/NG will affect the safety performance, such as the sensitivity and compatibility. [10][11][12][13][14][15] Particularly for high-energy and high-sensitivity nitrate esters, tiny changes in moisture content could have a great impact on the safety performance in practice.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, reducing the temperature coefficient is also an advantage of ETC ignition . The main research directions of plasma ignition include: the comparison between plasma ignition method and conventional ignition method, the control of propellants combustion, the design of plasma capillary, the effects of plasma parameters on energy input and propellants combustion, and the influence of different propellant formulations on the ignition process . Edwards et al.…”
Section: Introductionmentioning
confidence: 99%